Clinical supervision in podiatry in Australia and New Zealand: supervisor challenges in this role - Katrina Reynolds; Michelle McLean (BMC Medical Education, 2023)
Abstract Background Clinical supervisors play an integral role in preparing podiatry graduates for clinical practice. Not enough is, however, known about how prepared podiatry clinical supervisors are for this role, in terms of training received and the challenges they face in the role. Informed by previous qualitative research, this study extends our understanding of what it means to be a clinical supervisor in podiatry. Methods An online survey comprising closed and open-ended questions gathered data from 67 registered podiatrists who were also clinical supervisors. Descriptive analysis was undertaken. Chi-square analysis was used to test independence between preparedness for supervision and variables of interest (e.g. training received). Item analysis was assessed using Cronbach’s alpha coefficients and Kendall’s Tau to determine whether statistically significant associations existed across the broad challenges previously identified (i.e. supervisor-specific, curriculum and students). Open-ended comments were analysed using content analysis. Results Generally, most supervisors (64%, 43/67) initially felt “ prepared” to supervise, despite the majority (58%, 39/67) not having received any training or educational support. Overwhelming, supervisors (97%, 65/67) considered universities responsible for ensuring quality clinical supervision. They perceived many of the previously identified supervisor-specific challenges (e.g. time-consuming), curriculum issues (e.g. limited hands-on patient contact in private practice placements) and student deficiencies (e.g. poor time management). Positive correlations were found across the three sets of challenges, with the strongest measure of association found between overall student deficiencies and overall curriculum issues (p < .001). Conclusion These findings contribute to a deeper understanding of clinical supervision in podiatry. The study identified inconsistent support for clinical supervisors from partner universities. This study found a clear desire and need for supervisor training. A partnership approach is recommended in which universities work with clinical supervisors to address their overall challenges in terms of supervisor professional development, paying attention to curriculum issues, and improving student preparedness during placements.